New developed formula to calculate the permittivity of ferrite-polymer composite - Al-Habashi, Ramadan; Abbas, Zulkifly (Trans Tech Publications, 2013)
A new developed formula named the Habashi-Zul formula, based on the Maxwell-Garnett (MG) formula was fabricated and used to calculate the complex permittivity of the Sm-YIG in PVDF composite samples in the frequency range of 10 MHz to 1 GHz. The calculated permittivities results were compared with the measured values of each sample of Sm-YIG in PVDF composite samples and, with calculated results from various theoretical models including the MG, Looyenga, Bruggeman and, Sen Scala and Cohen. The Habashi-Zule formula presented higher accuracy as compared to other models.